(untitled) (Forum for Linguistic Studies, 2024)
This research is motivated by the phenomenon of the emergence of a gap between the demands of implementing the merdeka curriculum and the still low competence of teachers, while on the other hand, the function of academic supervision in improving teacher competence has not been optimal. This research is based on Terry’s management theory, Wiles’ supervision theory, Farmer’s supervision model, Spancer’s competency theory, and Ki Hajar Dewantara’s merdeka curriculum theory. The approach used is qualitative descriptive with a case research method, while the data collection techniques include observation, interviews, documentation studies, and triangulation. The research outcomes indicate: (1) the academic supervision planning of the school principal to improve teacher competence in implementing the independent curriculum is formulated based on G.R. Terry’s planning and is aligned with Data-Based Planning (PBD) policies; (2) the organization of academic supervision is carried out based on G.R. Terry’s organization, which is in line with the policy of utilizing the school’s seven assets in school development; (3) the implementation of academic supervision is in accordance with a plan based on Sanusi’s six life value systems; (4) the evaluation of academic supervision is consistent with G.R. Terry’s evaluation theory; (5) the problems of academic supervision by the school principal are well identified; (6) the solutions to academic supervision problems are highly effective in anticipating the issues faced and are aligned with the concept of IRB (Identification, Reflection, and Improvement). Based on the research outcomes, the academic supervision management by the school principal is capable of enhancing teacher competence in implementing the merdeka curriculum in the flagship schools..